Decomposing user-defined tasks in a reinforcement learning setup using TextWorld - Petsanis, Thanos; Keroglou, Christoforos; Ch. Kapoutsis, Athanasios; Kosmatopoulos, Elias B.; Sirakoulis, Georgios Ch. (Frontiers in Robotics and AI, 2023)
The current paper proposes a hierarchical reinforcement learning (HRL) method to decompose a complex task into simpler sub-tasks and leverage those to improve the training of an autonomous agent in a simulated environment. For practical reasons (i.e., illustrating purposes, easy implementation, user-friendly interface, and useful functionalities), we employ two Python frameworks called TextWorld and MiniGrid. MiniGrid functions as a 2D simulated representation of the real environment, while TextWorld functions as a high-level abstraction of this simulated environment. Training on this abstraction disentangles manipulation from navigation actions and allows us to design a dense reward function instead of a sparse reward function for the lower-level environment, which, as we show, improves the performance of training. Formal methods are utilized throughout the paper to establish that our algorithm is not prevented from deriving solutions.